“Experimental Study of M 25 concrete with Sugarcane Bagasse and sisal fibre” - Rajan Kumar Singh, Sharad Nigam, Tarun Kumar Rajak (Mathematical Statistician and Engineering Applications, 2022)
Since concrete is used more than any other material in the world, its use cannot be avoided. However, given the current shortage of natural resources, there is also a greater need for concrete. Because it helps to conserve natural resources, the use of industrial waste byproduct in structural concrete has been advocated. When compared to conventional concrete (without SBCA and Sisal fibre), the research studies showed that sisal fibre concretes were significantly improved in their flexural properties with strength gains for different mixes due to the inclusion of fibre up to 2% and also exhibited synergistic interaction effects due to SBCA combinations. The presence of sisal fibres in concrete showed in ductile failure with multiple splitting and bridging the crack formation, when reached an ultimate failure load. When reinforced structures use only Portland cement in their concrete and the rebar is not tightly interlocked, the structural building concrete corrosions are continually exposed to higher levels of deterioration. Additionally, corrosions may be brought on by the offered cover concrete’s insufficient depth. In these conditions, mineral admixtures are crucial to the construction industry. The use of pozzolanic activity of residue like sugarcane bagasse ash (SCBA) has exceptional strength, more stiffness, and remarkable durability; the average particle less than 45 microns replaced (0-20%), sisal fibres (2.0%), steel slag (0- 60%), along with 1.5% of super plasticizers by weight of binder content for various mixes of M25 grade of concrete was experimentally studied. This research work is focused on, how to increase the corrosion resistance and enhancing the matrix densification by using the accelerated corrosion technique by Florida method. The potential corrosion of steel rebar with SCBA shows the tremendous resistance impact towards the corrosion initiation period of cracks. It was clearly observed that 20% of SCBA with 40% of steel slag along with 2.0% of sisal fibres shows extensive performance effects on the RCPT for 7, 14 28 and 56 days of curing.